We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-1
38
2
avatar+44 

deleted

 Nov 7, 2019
edited by htzhang919  Nov 16, 2019

Best Answer 

 #1
avatar+19832 
+4

f(x) = 1 / (x-3)    

the g(x) = f( f(x) ) =   1 /  [1/(x-3) -3 ] = 1/  (1 -3x+9)/(x-3) =  (x-3) / (10-3x)        x cannot equal 10/3  (denominator would be 0)

 Nov 7, 2019
 #1
avatar+19832 
+4
Best Answer

f(x) = 1 / (x-3)    

the g(x) = f( f(x) ) =   1 /  [1/(x-3) -3 ] = 1/  (1 -3x+9)/(x-3) =  (x-3) / (10-3x)        x cannot equal 10/3  (denominator would be 0)

ElectricPavlov Nov 7, 2019
 #2
avatar+44 
+1

deleted

 Nov 8, 2019
edited by htzhang919  Nov 16, 2019

25 Online Users

avatar
avatar